Nurses' knowledge and attitudes toward pediatric pain assessment and management: a scoping systematic review from 2015 to 2025 - Haytham Al-Oran; Yousef Rubbai (Frontiers in Health Services, 2026)
Introduction Nurses play an essential role in providing care to patients, and having the necessary skills, knowledge, and attitudes for effective pain assessment and treatment is crucial for ensuring best patient outcomes. The purpose of this paper is to review recent research about current nurses' knowledge and attitude toward pediatric pain assessment and management in pediatric settings. Method The methodological approach taken in this paper is a scoping review using Arksey and O'Malley's five-step framework (2005). Databases including EBSCO host, PubMed, CINAHL, Springer, Cochrane, Science Direct, Ovid, and Google Scholar were searched to collect full-text articles available in English between 2015 and 2026. 20 out of 235 full-text papers met the inclusion criteria in the current scoping review. Results The synthesis of the results of the 20 included research studies revealed that nurses worldwide had poor knowledge and attitudes concerning pediatric pain assessment and management. Various tools were utilized to assess nurses' knowledge and attitudes. The majority of research adopted the use of true/false or multiple-choice questions, as well as Likert scales with acceptable validity and reliability. The most extensively utilized tool was the Knowledge and Attitudes Survey Regarding Pain. Conclusion This review's findings imply that pain education programs should be refined to enhance nurses' knowledge and attitudes toward pediatric pain assessment and management. Studies in the future should focus on recognizing individual and environmental features that influence nurses' level of knowledge and attitudes to improve the development of educational programs and the quality of care provided.